Conceptions of undergraduate Mathematics students about initial training for teaching with digital technologies at a university in Bahia - Ferreira, Kaio César de Santana (2025)
The use of digital technologies in the practice of the Mathematics teacher can promote meaningful learning, based on mathematical experimentation, as well as favor an active attitude of the student in the learning process. However, for digital technologies to effectively form part of teaching practice, teachers must experience teaching and learning with these resources in their training. Thus, this research proposes to investigate how undergraduate students in Mathematics have experienced the practice of digital technologies in the teaching and learning of Mathematics in their training. The theoretical basis is in the theoretical construct human-beings-with-media. This is a qualitative research whose procedure was the semi-structured interview. The participants were twenty undergraduate students in Mathematics from Santa Cruz State University. The analytical framework was Content Analysis. The emerging coding of the data resulted in five categories that represent the interviewees' conceptions about training for teaching with digital technologies in the aforementioned undergraduate course, namely: Mathematical visualization and domestication of media; Absence of technologies in Basic Education; Experimentation with technologies; Digital technologies saving the teaching of Mathematics; and Reformulation of the curriculum and continuing education. It is concluded that students lack the perception that technologies condition the construction of knowledge and have potential that goes beyond the motivation factor. Among the suggestions from participants for a degree course that prepares for teaching with digital technologies, are attention to the curriculum and updating of teacher trainers.